Cadaveric Study of the Anatomical Variations of the Accessory Pancreatic Duct - Shahriah, Sunjida; Nurunnabi, Abu Sadat Mohammad; Johora, Fatema; Siddiqua, Dilruba; Ara, Shamim (Journal of Bangladesh Society of Physiologist, 2015)
Background: The accessory pancreatic duct enters the duodenum at the minor duodenal papilla, developmentally draining the dorsal pancreatic bud; however, it is smaller and less constant than the main pancreatic duct and undergoes varying degrees of atrophy at the duodenal end. Objective: The objective of this study was to see the variations in course, opening and communication pattern of the accessory pancreatic duct in different age-groups in a Bangladeshi population. Methods: This crosssectional, descriptive study was done was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from August 2005 to December 2006, based on collection and dissection of 75 postmortem male human pancreas. The collected samples were divided into seven age groups: 10-19 years, 20-29 years,30-39 years, 40-49 years, 50-59 years),60-69 years and(e70 years. However, 65 samples were taken for final observation. Results: The accessory pancreatic duct was found in 27.69% specimens. Straight course was found in 50% specimen, while spindle course in 27.78% and cudgel course in 22.22% specimens were observed. In only 4 (6.15%) specimens, the accessory pancreatic duct communicates with the common bile duct, while in 11 (16.93%) specimens, the accessory pancreatic duct communicates with the main pancreatic duct. 12 (66.67%) accessory pancreatic ducts opened into the minor duodenal papilla, while 5 (27.78%) into the major duodenal papilla and 1 (5.55%) into the 3rd duodenal papilla. Conclusion: Several variations were observed in accessory pancreatic duct pattern in terms of their course, opening and communications. However, no significant differences were evident in any parameter among the age groups. Here, females were excluded due to less availability of the female cadaveric pancreas during study period. DOI: http://dx.doi.org/10.3329/jbsp.v9i2.22802 Bangladesh Soc Physiol. 2014, December; 9(2): 83-88